Analisis Isu Strategis Rancangan Teknokratik RPJMD Kabupaten Badung Tahun 2025-2029 - Budiarsana, Komang (Green Publisher Indonesia, 2024)
The writing of this policy paper is to describe the formulation of strategic issues for medium-term development planning in Badung Regency in 2025-2029. This study uses a qualitative method, namely an in-depth data processing method with data from observations, and literature. There are ten strategic issues of the 2025-2029 Badung Regency RPJMD technocratic design which are produced through weighting based on their linkage with global, national and Bali Province strategic issues, namely: geopolitics and geoeconomics; conversion of agricultural land; blue economy; Environment; technological developments; population explosion; climate change and disasters; public service infrastructure; green workforce; and talent management. The suggestion that can be implemented is that the Badung Regency Government needs to carry out a more in-depth discussion on the strategic issue of the 2025-2029 Badung Regency RPJMD technocratic design together with all regional apparatus and related stakeholders so that the development of Badung Regency has the right goals and objectives and can answer development problems in the next five years.